Native Tissue Repair for Incontinence and Prolapse - Zimmern, Philippe E.; De, Elise J. B. (Springer International Publishing : Imprint: Springer, 2017)
This book demonstrates knowledge on tissue-based procedures for stress urinary incontinence and other pelvic floor related topics. As the field shifts away from using synthetic material for repair, this work presents a new perspective on native tissue repair from the opinions and research of the authors. Written by a panel of expert authors in the field, this text provides high quality, focused information. With established track records the authors illustrate how to perform the procedure vaginally or through open surgery, and inclusion of live surgeries via online video, makes this an invaluable tool for busy surgeons and specialists interested in pelvic floor reconstruction. .
Keywords: Medicine.; Gynecology.; Rectum -- Surgery.; Minimally invasive surgery.; elektronické knihy; electronic books